MALE ROMANCE FORMULA IN FORREST GUMP MOVIE (1994) - Vidi Rutsyamsun; Lili Awaludin (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2023)
This journal investigates how Forrest Gump's portrayal of disability in romantic relationships. To investigate how the main character, Forrest Gump, and his partner, Jenny, encountered difficulties in forging a love relationship because of Forrest's disabilities, the researcher employed a qualitative technique with a narrative analytic method. The study sought to investigate how the movie deals with disability difficulties while presenting the ideal romance formula. The study also discovered that the Forrest Gump movie adheres to Janice Radway's ideal romance formula while adapting it to the disability setting. The individuals' personalities are given more depth by this extra complexity, which also advances the story as a whole. The Forrest Gump movie accurately, tenderly, and meaningfully shows romantic connections between individuals with impairments, according to the study. Forrest's intellectual impairment isn't the main focus of his persona; rather, it's only one facet of who he is. The movie demonstrates that Forrest is a loving, kind, and sympathetic individual who is able to develop lasting connections despite his impairment. Jenny's reaction to Forrest's impairment is honestly portrayed in the movie, and she first has second thoughts about dating him. She comes to see, nevertheless, that Forrest's impairment is only one aspect of him and does not characterize him as a person as their relationship progresses.